Relation of the double‐ITCZ bias to the atmospheric energy budget in climate models. Issue 14 (18th July 2016) - Adam, Ori; Schneider, Tapio; Brient, Florent; Bischoff, Tobias
Abstract: We examine how tropical zonal mean precipitation biases in current climate models relate to the atmospheric energy budget. Both hemispherically symmetric and antisymmetric tropical precipitation biases contribute to the well‐known double‐Intertropical Convergence Zone (ITCZ) bias; however, they have distinct signatures in the energy budget. Hemispherically symmetric biases in tropical precipitation are proportional to biases in the equatorial net energy input; hemispherically antisymmetric biases are proportional to the atmospheric energy transport across the equator. Both relations can be understood within the framework of recently developed theories. Atmospheric net energy input biases in the deep tropics shape both the symmetric and antisymmetric components of the double‐ITCZ bias. Potential causes of these energetic biases and their variation across climate models are discussed. Key Points: CMIP5 precipitation biases have significant hemispherically symmetric and antisymmetric components Hemispherically antisymmetric biases are related to the cross‐equatorial atmospheric energy flux Hemispherically symmetric biases are related to the atmospheric net energy input near the equator